CD4 recovery following antiretroviral treatment interruptions in children and adolescents with HIV infection in Europe and Thailand. Issue 7 (16th May 2019) - ,
Abstract : Objectives: The aim of the study was to explore factors associated with CD4 percentage (CD4%) reconstitution following treatment interruptions (TIs) of antiretroviral therapy (ART). Methods: Data from paediatric HIV‐infected cohorts across 17 countries in Europe and Thailand were pooled. Children on combination ART (cART; at least three drugs from at least two classes) for > 6 months before TI of ≥ 30 days while aged < 18 years were included. CD4% at restart of ART (r‐ART) and in the long term (up to 24 months after r‐ART) following the first TI was modelled using asymptotic regression. Results: In 779 children with at least one TI, the median age at first TI was 10.1 [interquartile range (IQR) 6.4, 13.6] years and the mean CD4% was 27.3% [standard deviation (SD) 11.0%]; the median TI duration was 9.0 (IQR 3.5, 22.5) months. In regression analysis, the mean CD4% was 19.2% [95% confidence interval (CI) 18.3, 20.1%] at r‐ART, and 27.1% (26.2, 27.9%) in the long term, with half this increase in the first 6 months. r‐ART and long‐term CD4% values were highest in female patients and in children aged < 3 years at the start of TI. Long‐term CD4% was highest in those with a TI lasting 1 to <3 months, those with r‐ART after year 2000 and those with a CD4% nadir ≥ 25% (all P  < 0.001). The effect of CD4% nadir during the TI differed significantly ( P  = 0.038) by viral suppression at the start of the TI; in children with CD4% nadir < 15% during TI, recovery was better in those virally suppressed prior to the TI; viral suppression was not associated with recovery in children with CD4% nadir ≥ 25%. Conclusions: After restart of ART following TI, most children reconstituted well immunologically. Nevertheless, several factors predicted better immunological reconstitution, including younger age and higher nadir CD4% during TI.